The Housing Enabler instrument: Assessing threats to reliability and validity. (January 2019) - Norin, Lizette; Iwarsson, Susanne; Haak, Maria; Slaug, Björn
Introduction: The Housing Enabler instrument, designed to measure housing accessibility, has not been used in samples with long-standing spinal cord injury. We aimed to investigate potential threats to the reliability and validity of the instrument when used among older adults with spinal cord injury. Method: Cross-sectional data from the Swedish Aging with Spinal Cord Injury Study ( N  = 123, injury levels C1–L5) were utilised. The potential effect on the reliability and content validity of the House Enabler was qualitatively considered and reviewed in an iterative evaluation procedure. To analyse the potential effect on construct validity, simulations adjusting accessibility problem scores for housing adaptations and use of mobility devices were conducted. Findings: Considerable threats to the reliability and content validity of the Housing Enabler were identified. The simulated analysis of construct validity showed a modest overall effect on the accessibility problem scores, although this was substantial in some individuals. Conclusion: Data collection and analyses of housing accessibility with the Housing Enabler in samples characterised by high frequencies of housing adaptations and/or use of mobility devices (such as powered wheelchairs) require particular attention. Further studies are needed to propose optimisation of the instrument for use in such contexts, followed by psychometric testing to maintain reliability and validity.